A Combined Approach using Sonochemistry and Photocatalysis: How to Apply Sonophotocatalysis for Biomass Conversion?. Issue 14 (1st June 2017) - Chatel, Gregory; Valange, Sabine; Behling, Ronan; Colmenares, Juan Carlos
Abstract: The innovative combination of sonochemistry (power ultrasound) and photocatalysis (UV light) has been extensively investigated in the literature, especially as an advanced oxidation process. Based on these results but with a completely different strategy, the sonophotocatalysis starts to be applied to organic reactions and could represent an innovative way to valorize biomass into fuels or platform molecules. This article discusses this opportunity and proposes some trends and outlooks for further researches in the area. Abstract : Sound and light for a nice show ! The combination of sonochemistry (power ultrasound) and photocatalysis (UV light) represents an innovative way to valorize biomass into fuels or platform molecules… but how to proceed?